In situ phase transformation synthesis of unique Janus Ag2O/Ag2CO3 heterojunction photocatalyst with improved photocatalytic properties - Jo, Wan-Kuen; Kumar, Santosh; Yadav, Poonam; Tonda, Surendar (Applied Surface Science, 2018)
Herein, Ag2O/Ag2CO3 nanocomposite with unique Janus morphology was synthesized by a facile ion-exchange followed by an in situ phase transformation method with precise control of its nucleation and growth processes. Contrary to conventional synthetic procedures of Janus architectures, the present Janus system was constructed without the need for surfactants or toxic chemicals. Most importantly, the visible-light-absorbing Janus Ag2O/Ag2CO3 nanocomposite exhibits a remarkable performance toward the degradation of Rhodamine B and 4-chlorophenol, far superior to that observed for bare Ag2CO3. The obvious enhancement of the photocatalytic performance of this nanocomposite is mainly attributed to the intimate Ag2O/Ag2CO3 interface created by its exceptional Janus architecture, which in turn allows for rapid charge transfer processes. Additionally, the Janus system exhibited a high photostability during recycling experiments with no significant change in the degradation activity. (C) 2018 Published by Elsevier B.V.

Investigations into the nucleation dynamics of the stable Na-metal anode: revealing the role of a tin-infused carbon nanofiber interlayer - Wasnik, Kundan; Yadav, Poonam; Ahuja, Manuj; Mirzapure, Vinay; Johari, Priya; Shelke, Manjusha V. (ACS Applied Materials & Interfaces, 2025)
Fundamental understanding and controlling of sodium nucleation are essential for enhancing the performance, safety, and longevity of sodium metal batteries, which is not yet clearly understood in the case of sodium metal batteries. The present study showcases how a modification in the host material influences nucleation kinetics. Current-time transient studies on copper, carbon nanofiber, and tin-embedded carbon nanofiber interlayers employing the Scharifker-Hills model elucidate the mode of nucleation. This work tries to delve deep and presents a case study on how a tin-based interlayer can not only minimize the barrier for sodium nucleation but also direct the sequential progressive and instantaneous nucleation of sodium metal while reducing the overpotential substantially, resulting in crystalline, uniform Na-metal deposition. Further, to account for the complex dynamics of solid electrolyte interphase (SEI) formation distinctly associated with alkali metal deposition, the SEI-fracture model has been included, and the quantification of electrochemical nucleation parameters is obtained. The results provide important insights into the sodium nucleation mechanism, paving the way to counter dendrite formation and SEI dissolution issues of the Na-metal anode.
Keywords: overpotential; progressiveand instantaneous nucleation; Scharifker-Hills model; SEI-fracture model; tin interlayer